Effect of Brand Awareness, Celebrity Endorsements, and Online Customer Reviews on Women's Choice to Purchase Skincare Products on TikTok: Study of Gen Z Women in Bandar Lampung - Pratiwi, Merliana; Rifa'i, Ahmad; Aprilani, Deddy (Journal of Business Management and Economic Development, 2025)
The marketing industry has changed as a result of the quick advancement of digital technology, and TikTok is now utilized as an efficient marketing tool in addition to being an entertainment platform. Additionally, TikTok serves as a platform for brand-consumer connection as they look for information and make judgments about what to buy. This study is to investigate how women's skincare shopping decisions on TikTok are influenced by brand awareness, celebrity endorsements, and online customer evaluations, with a particular focus on Gen Z women in Bandar Lampung. All Bandar Lampung City Gen Z women who have purchased Skintific skincare items on TikTok at least once make up the study's population. The study uses a quantitative framework and explanatory methodologies. The samples were selected using purposeful sampling, and the sampling process was conducted using accidental sampling. 97 participants were given questionnaires as part of the data collection process. Among the data analysis techniques used are the validity test, reliability test, multiple linear regression analysis, classical assumption test, and hypothesis test. The data was statistically descriptively analyzed using SPSS software version 27. The results show that, when taken into account separately, brand awareness, celebrity endorsements, and online customer reviews all significantly and favorably influence purchasing decisions. When taken as a whole, these three elements have a favorable and substantial impact on purchasing decisions.